2015
DOI: 10.12816/0013178
|View full text |Cite
|
Sign up to set email alerts
|

Keros Classification among Jordanian Population

Abstract: Objectives: To evaluate the prevalence of each KEROS subclass among Jordanian population, and to compare between subclass distribution in right and left side, and also between different genders. Methods: Retrospectively evaluating computed tomography studies for paranasal sinuses of 100 different patients, the depth of lateral lamellae of cribriform plate was measured and this was plotted against the different subtypes of Keros classes considering gender variations. Results: The favorable classes were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…The comparison of the frequency of the different type of Keros on the right & left sides in males and females indicate that Keros type II was found to be the most frequent in both genders on both sides. Our results are in accordance with a few other studies 1,8,23,24 who also reported the highest frequency of type II Keros on both sides in both genders. Elwany et al report a higher frequency of type II Keros on both sides in the male gender only.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The comparison of the frequency of the different type of Keros on the right & left sides in males and females indicate that Keros type II was found to be the most frequent in both genders on both sides. Our results are in accordance with a few other studies 1,8,23,24 who also reported the highest frequency of type II Keros on both sides in both genders. Elwany et al report a higher frequency of type II Keros on both sides in the male gender only.…”
Section: Discussionsupporting
confidence: 94%
“…However, our study reports the least frequency of type I Keros on both sides in both genders. For some studies type, I remain to be the second-highest on both the sides in both genders 23,24 , for others type I remains to be second highest in males only. 8,22 Such variation may be due to racial differences and also could be due to the fact that Keros classification is ambiguous in the ranges of 3-4mm and 7-8mm.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study showed that the height of LLCP on right side was 3.331+/-5.010mm, whereas on le side, it was 2.845+/-1.084mm.This differs from other studies as most of the 10,[12][13][14][15][16][17][18][19][20][21][22] studies had LLCP of >4mm.…”
Section: Discussionmentioning
confidence: 68%
“…2,3 The purpose of this research is to assess variations in these parameters and their surgical significance during endoscopic sinus surgery. [2][3][4][5]…”
Section: Introductionmentioning
confidence: 99%